Foreign direct investment and home-country political risk: the case of Brazil - Aguiar, S.; Aguiar-Conraria, L.; Gulamhussen, M. A.; Magalhães, Pedro (Latin American Research Review, 2012)
This article looks into the factors that explain foreign direct investment (FDI) in Brazil by country of origin. We collected a sample of 180 countries with and without FDI in Brazil. We use multiple estimation techniques and controls to isolate the effect of country political risk on outward foreign direct investment and show that countries with lower levels of political risk undertake more FDI in Brazil, and that features of the policy environment of home countries drive the negative relationship between risk and FDI. Furthermore, we show that the aspect of the political and institutional environment that is most likely to drive this negative relation between risk and investment into Brazil is related to the effectiveness of national governments. Our findings broaden the understanding of the puzzling influence of political risk on FDI observed in previous studies, correct for sampling and selection biases, and have substantive implications for policy design to attract FDI.